Reduced levels of S-nitrosothiols in plasma of patients with systemic sclerosis and Raynaud's phenomenon - Kundu, Devi; Abraham, David; Black, Carol M.; Denton, Christopher P.; Bruckdorfer, K. Richard (Vascular pharmacology, 2014)
S-Nitrosothiols (RSNOs) are bioactive forms of nitric oxide which are involved in cell signalling and redox regulation of vascular function. Circulating S-nitrosothiols are predominantly in the form of S-nitrosoalbumin. In this study plasma concentrations of S-nitrosothiols were measured in patients with systemic sclerosis (SSc) where NO metabolism is known to be abnormal. Venous blood was collected from 16 patients with Raynaud's phenomenon (RP), 45 with systemic sclerosis (SSc) (34 patients had limited SSc (IcSSc) and 11 diffuse cutaneous disease (dcSSc)). Twenty six healthy subjects were used as controls. Plasma S-nitrosothiol concentrations were measured by chemiluminescence. The measurements were related to the extent of biological age, capillary/skin scores and disease duration. Plasma RSNO levels in patients with Raynaud's phenomenon (RP) and in those with SSc was significantly lower compared to the concentrations in control subjects. In SSc, plasma S-nitrosothiols were often below the level of detection (1nM). Low S-nitrosothiol concentrations were observed in the blood of patients with SSc and patients with RP indicating a profound disturbance of nitric oxide metabolism. Chemiluminescence techniques were used to show that plasma levels of S-nitrosothiols were low in patients with Raynaud's phenomenon and in systemic sclerosis and in the latter were negatively related to age, capillary/skin scores and disease duration. [Display omitted]